Business Plan Preparation Training for Prospective Young Entrepreneurs - Waqiah, Waqiah; Sukini, Sukini; Hasyim Mahmud Wantu; Tomi Apra santosa; Unpris Yastanti (Universitas Pahlawan Tuanku Tambusai, 2024)
The purpose of community service is to increase the effectiveness of business plan preparation training for prospective young entrepreneurs. This training was carried out with a participatory method that involved simulating the preparation of a business plan, group discussions, and guidance from business experts. The training participants consisted of 10 young entrepreneurial candidates who were selected based on their interests and entrepreneurial potential. The results of the study show that this training has succeeded in improving the knowledge and skills of participants in developing an effective business plan. Prior to the training, the majority of participants only had a basic understanding of the components of a business plan. However, after participating in the training, participants are able to develop a business plan that includes market analysis, marketing strategy, operational management, financial projections, and risk analysis well. In addition, this training also encourages increased confidence of participants in starting and managing their businesses.